(untitled) (Architecture Image Studies, 2025)
Healthcare systems face rural–urban workforce imbalances and efficiency gaps. Knowledge-sharing among clinicians is a key lever to improve service quality. Drawing on Social Exchange Theory, this study examines how career advancement (CA) opportunities and job characteristics (JC) influence knowledge-sharing behavior (KSB), and whether subjective norms (SN) amplify these effects. A cross-sectional survey was conducted in 2019 among healthcare professionals from eight public hospitals in Laos. Of 450 questionnaires distributed, 310 valid responses were obtained (68% response rate). Respondents were mainly nurses (71%) and doctors (29%), with most aged 21–30 years. Validated scales measured CA, JC, SN, and KSB on a five-point Likert scale. Data was analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test reliability, validity, and hypothesized relationships. All constructs showed strong reliability (CR = 0.85–0.91) and validity (AVE = 0.53–0.70). Structural analysis confirmed positive effects of CA (β = 0.189, p < 0.05), JC (β = 0.272, p < 0.01), and SN (β = 0.416, p < 0.01) on KSB. Mediation tests showed that SN strengthened the effects of CA (β = 0.232, p < 0.01) and JC (β = 0.376, p < 0.01) on knowledge-sharing. Findings highlight that supportive job design, clear career pathways, and organizational norms foster knowledge-sharing among healthcare staff. Both CA and JC directly and indirectly (via SN) promote KSB. Administrators should prioritize structured career development, supportive job design, and norm-building initiatives such as leadership endorsement and peer recognition. Future research should explore these relationships in varied contexts and test demographic moderators to enhance generalizability.